PENGARUH FAKTOR SOSIAL PADA KEPUASAN HIDUP DALAM LINGKUNGAN TENAGA AKADEMIK PERGURUAN TINGGI - Yoyok Soesatyo (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2013)
There are problems of life satisfaction in the academic personnel of public universities in East Java. Therefore, this study aims to determine the management of social factors, namely social capital, social capital benefits and human capital to the life satisfaction of academic personal.And to test the conceptual model of the research. Methods used to obtain data Cronbach’s Alpha and the search result was around 0,6654–0,8854. Collected data was analyzed using Structural Equation Modeling (SEM) to test the problems, test the objective and test the hypothesis. This result indicate that (a) the three factors of social capital (social capital benefit, human capital) have significant impact on life satisfaction. Minimum rate score above 3 to near 5. (b) Social capital and life satisfaction have significant correlation 0,037 of star sign. (c) Social capital and social capital benefit have no significant correlation 0,065. (d) Social capital and human capital have significant correlation 0,040. (e) Social capital benefit and life satisfaction have significant correlation 0,045. (f) Human capital and life satisfaction have significant correlation 0,042 and to fulfilled at least 2 criterias good fit measure: Probability, RMSEA and TLI.